ANALISIS PERBANDINGAN TPAK DAN TPT TERHADAP KEMISKINAN DI GERBANGKERTOSUSILA TAHUN 2019-2023 - ALFIYANI, NUR; SYAWALUDIN, MUHAMMAD (Ganec Swara, 2025)
This study analyzes the comparison between Labor Force Participation Rate (LFPR), Open Unemployment Rate (OUR), and poverty levels in the Gerbangkertosusila region during 2019-2023. Using a quantitative descriptive analysis method with a comparative approach, this research processes secondary data from the East Java Provincial Statistics Office. The results show an increase in LFPR across all regions, with Lamongan recording the highest increase from 68.96% to 75.08%. OUR experienced a significant spike in 2020, particularly in Sidoarjo (10.97%) and Surabaya (9.79%), correlating with increased poverty. Bangkalan consistently had the highest poverty rate (21.57% in 2021), while Surabaya had the lowest (4.51% in 2019). Although most regions showed declining poverty rates since 2021, significant disparities remain. This study concludes that the relationship between employment indicators and poverty is complex, emphasizing the importance of poverty reduction strategies tailored to local contexts to address regional inequalities